Analysis of risk factors for pneumonia in patients with catatonia: a cross-sectional analysis - Meng, Qingpeng; Zhou, Danna; Zhao, Xixi; Wang, Jing; Yin, Li; Liang, Sixiang; Ji, Xiao (Frontiers in Psychiatry, 2024)
Objective The clinical management of catatonia has always been a focus of psychiatric nursing. Unfortunately, there is still limited research on the risk factors and nursing methods for patients with catatonia and bacterial pneumonia. Few studies have identified and analyzed the clinical risk factors for catatonia patients with bacterial pneumonia. This study aims to explore the risk factors and preventive nursing measures for pneumonia in patients with catatonia. Methods A total of 88 patients with catatonia treated in the emergency department of a psychiatric hospital from January 2019 to October 2021 were selected. They were divided into bacterial pneumonia group (n=17) and non-pneumonia group (n=71) based on whether they had pneumonia. The demographic data and clinical characteristics of the two groups were compared. Logistic regression analysis and point-biserial correlation were used to analyze the risk factors for developing pneumonia in patients with catatonia. Results The incidence of pneumonia in patients with catatonia was 19.32%. Correlation analysis showed that age (r=0.216, p=0.043), The Activities of Daily Living Scale (ADL) score (r=0.265, p=0.013), cell count of white blood (r=0.591, p<0.001), neutrophil count (r=0.599, p<0.001), percentage of neutrophils (r=0.311, p=0.003), C-reactive protein (r=0.558, p<0.001), bedridden days (r=0.470, p<0.001), and albumin level (r=-0.288, p=0.007) were significantly associated with pneumonia. Multivariate logistic regression analysis showed that smoking, bedridden days, family support, and nutritional status were risk factors for pneumonia in patients with catatonia. Conclusion Reducing smoking and bedridden days, improving nutrition, and providing timely preventive nursing care by family members can reduce the occurrence of pneumonia in patients with catatonia.